Systematic Literature Review: The Contribution of Metaverse Contextual Economic Learning to Human Development in the Future - Eka Indah Nurlaili; Albrian Fiky Prakoso; Amirul Arif; Eka Hendi Andriansyah; Dhiah Fitrayati; Muhammad Abdul Ghofur; Arina Salsabilla Haq (IKIP Widya Darma Surabaya, 2023)
Objective: This study aims to determine the contribution of economics education in tertiary institutions to human development in the future. Method: This type of research is included in the type of literature review research. The process of identifying and selecting articles started with 382 articles found on the Google Scholar index and published from 2017 to 2022. Then, they were selected for eligibility, so eight articles were selected. Articles are also selected based on the credibility of the journal, namely those that are nationally accredited by Sinta. Results: The results obtained show that this metaverse contextual learning can make economic education a beacon of human development in the future. In lectures, students get a good understanding of the material, and it also has an impact on their learning outcomes. Novelty: The most important thing is that students have been taught about market structure, which then boils down to generating business ideas in the context of the metaverse so that one day they become successful entrepreneurs in the metaverse era.